Clinical aspects of co-infection by HIV and syphilis in pregnancy and exposure in newborn intended at Pediatric Hospital of Santa Catarina - Kuerten Pamplona da Silva, Laura; Kuhnen Dutra, Maria Julia; Kellers de Souza , Julia; Prohmann de Carvalho, Aroldo; Maria de Faria, Sônia; Rocha Carvalho, Emanuela (Brazilian Journal of Sexually Transmitted Diseases, 2024)
Introduction: Sexually transmitted infections frequently affect pregnant women and, consequently, newborns. HIV and syphilis are vertically transmitted to children and co-infection requires special attention due to its clinical implications. Objective: To describe clinical aspects of HIV/syphilis coinfection during pregnancy and the exposure of newborns to infections treated at a pediatric reference hospital in Santa Catarina between 2015 and 2020. Methods: Observational, descriptive study, secondary to a line of research “Epidemiological description of children exposed to HIV” from January 2015 to December 2020 in a tertiary pediatric hospital in Santa Catarina. Results: 678 medical records were analyzed with ICD Z.206 (contact with and exposure to HIV), in which 71 (10.5%) newborns were exposed to HIV and Syphilis co-infection. Of these, 37 (52.1%) were male, 14 (19.7%) confirmed a diagnosis of HIV and 30 (42.2%) of congenital syphilis. Of the co-infected pregnant women, 38 (53.5%) were diagnosed with HIV prior to pregnancy, 53 (74.6%) used ART and 40 (52.1%) used harmful substances. Furthermore, 34 (46.4%) pregnant women had a minimum number of 6 prenatal consultations, 35 (49.3%) had vaginal births and 29 (40.8%) had undetectable HIV RNA quantification at the time of delivery. HIV prophylaxis for newborns occurred in 66 (92.9%) of cases. Conclusion: It is concluded that the studied population was mostly made up of pregnant women who were diagnosed with HIV infection prior to pregnancy. Of these, the majority were using ART, but the minority carried out the minimum number of consultations recommended by the Ministry of Health. Regarding newborns, the majority received HIV prophylaxis.